Perempuan Pelestari Budaya - Santoso, Agus; Pratama, Muhamad Tris Hadi (Masyarakat Sejarawan Indonesia, 2021)
The development of women's history must continue to be improved due to the lack of availability of sources that record women's roles in Indonesian history. Faced with that condition, the oral history method is present as an alternative source to answer the shortage of these sources. Recognizing the importance of oral history, the National Archives of the Republic of Indonesia (ANRI) is a national archival institution that maintains and preserves authentic sources in the form of archives from various mediums and carries out oral history interviews to complete and fill in the gaps of certain events that have occurred in Indonesia. the past. Regarding women's progress, ANRI's oral history interview with the theme of the Relatives of the Kingdom of the Nusantara shows the role of women in cultural preservation. ANRI interviewed three female sources from three different kingdoms, namely G.R.Ay. Retno Rosati Kadarisman Notohadiningrat from Mangkunegaran, GKR Koes Murtiyah Wandansari from Surakarta, and Anak Agung Ayu Dewi Girindra Wardani from Karangasem. This article discusses how ANRI's oral history activities led to the role of women in the Kingdom of the Nusantara in cultural preservation so that it can be an alternative source as a complement to the ANRI archive treasures that are useful to be used today and in the future. Keywords: Oral History, Women of the Kingdom of the Nusantara, Cultural Preservation